Targeting the sensory feedback within the swallowing network—Reversing artificially induced pharyngolaryngeal hypesthesia by central and peripheral stimulation strategies. Issue 2 (17th October 2020) - Muhle, Paul; Labeit, Bendix; Wollbrink, Andreas; Claus, Inga; Warnecke, Tobias; Wolters, Carsten H.; Gross, Joachim; Dziewas, Rainer; Suntrup‐Krueger, Sonja
Abstract: Pharyngolaryngeal hypesthesia is a major reason for dysphagia in various neurological diseases. Emerging neuromodulation devices have shown potential to foster dysphagia rehabilitation, but the optimal treatment strategy is unknown. Because functional imaging studies are difficult to conduct in severely ill patients, we induced a virtual sensory lesion in healthy volunteers and evaluated the effects of central and peripheral neurostimulation techniques. In a sham‐controlled intervention study with crossover design on 10 participants, we tested the potential of (peripheral) pharyngeal electrical stimulation (PES) and (central) transcranial direct current stimulation (tDCS) to revert the effects of lidocaine‐induced pharyngolaryngeal hypesthesia on central sensorimotor processing. Changes were observed during pharyngeal air‐pulse stimulation and voluntary swallowing applying magnetoencephalography before and after the interventions. PES induced a significant ( p < .05) increase of activation during swallowing in the bihemispheric sensorimotor network in alpha and low gamma frequency ranges, peaking in the right premotor and left primary sensory area, respectively. With pneumatic stimulation, significant activation increase was found after PES in high gamma peaking in the left premotor area. Significant changes of brain activation after tDCS could neither be detected for pneumatic stimulation nor for swallowing. Due to the peripheral cause of dysphagia in this model, PES was able to revert the detrimental effects of reduced sensory input on central processing, whereas tDCS was not. Results may have implications for therapeutic decisions in the clinical context. Abstract : Pharyngolaryngeal hypesthesia is a major reason for dysphagia in various neurological diseases. Here, we investigated whether pharyngeal electrical stimulation (PES) or transcranial direct current stimulation can revert the effects of experimentally induced pharyngeal hypesthesia on cortical activation in healthy adults in a crossover sham‐controlled design by means of magnetoencephalography. PES was able to revert the detrimental effects of reduced sensory input on central processing, whereas transcranial direct current stimulation was not.